2015
DOI: 10.3390/fi7030294
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Educational Opportunities with Computer-Mediated Assessment Feedback

Abstract: Abstract:As internet technologies make their way into developing areas, so too does the possibility of education and training being delivered to the people living in those previously unserved areas. The growing catalogue of free, high quality courseware, when combined with the newly acquired means of delivery, creates the potential for millions of people in the developing world to acquire a good education. Yet a good education obviously requires more than simply delivering information; students must also recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…With the progress of technology development, CMF, which is teachers’ manual feedback via computer, has drawn attention as promising support for language learners’ performance improvement such as speaking or writing skills in a computer-assisted language learning (CALL) environment (Tuffley & Antonio, 2015 ). However, the effect of CMF in a large-scale class is still unclear.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progress of technology development, CMF, which is teachers’ manual feedback via computer, has drawn attention as promising support for language learners’ performance improvement such as speaking or writing skills in a computer-assisted language learning (CALL) environment (Tuffley & Antonio, 2015 ). However, the effect of CMF in a large-scale class is still unclear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ideally, students need high-quality feedback on their assessment in any field. Although generating high-quality feedback is labour-intensive (Ashwell & Elam, 2017 ), Tuffley and Antonio ( 2015 ) insist that computer-mediated assessment and CMF via an LMS integration are cost-effective and can be applied to large-scale courses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the importance of feedback mechanisms in VLE, Tuffley and Antonio (2015) verify whether feedback can be automated through such platforms, and address the need for quality feedback, since it does not meet the expectations of students. According to Tuffley and Antonio (2015), a good return or return must: have predefined and clear evaluation criteria; possibilitate self-evaluation in relation to the expectations of the proposed task; provide performance information; stimulate discussion and questioning of academics; generate motivation and self-esteem; continuous improvement in academic performance. The result of the use of such mechanisms in educational platforms has demonstrated that they have a strong potential, being a tool that allows learning to learn.…”
Section: Lopez Andmentioning
confidence: 99%
“…The VLE should provide structured and immediate feedback; Robb and Fisher, 2015;Tuffley and Antonio, 2015;Laflen and Smith, 2017.…”
Section: Good Practices Authorsmentioning
confidence: 99%
See 1 more Smart Citation